2021
DOI: 10.1111/fwb.13736
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐term environmental changes influence age‐specific survival estimates in a salmonid population

Abstract: 1. Human-induced environmental change is a major stressor on freshwater habitats that has resulted in the population declines of many freshwater species.Ontogenetic shifts in habitat use and associated (st)age-specific requirements mean that impacts of environmental stressors can influence (st)ages in a population differently, and yet relatively few studies of freshwater fish populations account for their detail.2. We aimed to identify environmental and biotic factors affecting survival estimated for six age-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Deegan et al (1999) found that in arctic streams, Arctic Grayling tended to be larger in years with warmer mean river temperatures. Similarly, Marsh et al (2021) found that the growth of wild European Grayling was positively correlated with temperature; warmer years benefited juvenile growth but were negatively correlated to survival in adults, suggesting that temperatures above optimal were present in warmer years.…”
Section: Growth Proximate Composition and Survivalmentioning
confidence: 89%
“…Deegan et al (1999) found that in arctic streams, Arctic Grayling tended to be larger in years with warmer mean river temperatures. Similarly, Marsh et al (2021) found that the growth of wild European Grayling was positively correlated with temperature; warmer years benefited juvenile growth but were negatively correlated to survival in adults, suggesting that temperatures above optimal were present in warmer years.…”
Section: Growth Proximate Composition and Survivalmentioning
confidence: 89%
“…Special Areas of Conservation and Sites of Special Scientific Interest). There are also concerns over perceived declines in some barbel Barbus barbus (L.) and grayling Thymallus thymallus (L.) populations (Antognazza et al, 2016; Marsh et al, 2021), despite being classified as Least Concern at regional level, and in the abundance of sea trout. If assessed as a separate taxonomic entity, rather than the anadromous form of brown trout, sea trout would have been classified as Vulnerable (VU A2b).…”
Section: Discussionmentioning
confidence: 99%
“…populations (Antognazza et al, 2016;Marsh et al, 2021), despite being classified as Least Concern at regional level, and in the abundance of sea trout. If assessed as a separate taxonomic entity, rather than the anadromous form of brown trout, sea trout would have been classified as Vulnerable (VU A2b).…”
Section: Extinction Risks and Threatsmentioning
confidence: 99%